Contract for the International Carriage of Goods by Road - Tincani, Chiara (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book discusses the intensification of international transport services as the consequence of an increasingly capillary economic integration. In particular, in some European countries, such as Belgium, the Rhine area of Germany, and Denmark, the application of the Geneva Convention on the carriage of goods from the case law point of view is even more thorough than that of national law. Even though this is not the case for all countries, the Geneva Convention is a core text both for the scientific debates on the issue and for commercial operators. Therefore, proposing an up-to-date reading of the Convention is of utmost importance from the practical point of view, especially considering that, thanks to the consistent application of the International Carriage of Goods by Road contract, the Convention has become an essential prerequisite for the development of traffic. In ten chapters, this book reviews the Convention's structure and considers the case-law approaches and trends of most countries belonging to the European Union. It covers contracts and different negotiating models as well as compensation, liability of the carrier, and damages.
Chapter 1. Contract for the International Carriage of Goods by Road -- Chapter 2. The Mandatory Nature of the Geneva Convention -- Chapter 3. Stipulation of the Contract and the Consignment Note -- Chapter 4. The Different Negotiation Models and the Participation of Several Subjects in the Stipulation and Execution of Multiple Modes of Transport -- Chapter 5. The Journey and Execution of the Contract -- Chapter 6. Charges -- Chapter 7. Liability of the Carrier -- Chapter 8. Damages and Compensation Limit -- Chapter 9. Rights Protection -- Chapter 10. The Jurisdiction. .
Keywords: Private international law; Conflict of laws; International law; Comparative law; Commercial law; Civil law; Law of the sea; Aeronautics-Law and legislation; Law-Europe.; Private International Law, International and Foreign Law, Comparative Law; Business Law; Civil Law; Law of the Sea, Air and Outer Space; European Law